Chemically Homogenous Compounds with Antagonistic Properties at All α1-Adrenoceptor Subtypes but not β1-Adrenoceptor Attenuate Adrenaline-Induced Arrhythmia in Rats - Pytka, Karolina; Lustyk, Klaudia; Żmudzka, Elżbieta; Kotańska, Magdalena; Siwek, Agata; Zygmunt, Małgorzata; Dziedziczak, Agnieszka; Śniecikowska, Joanna; Olczyk, Adrian; Gałuszka, Adam; Śmieja, Jarosław; Waszkielewicz, Anna M.; et al. (Frontiers in Pharmacology, 2016)
Studies proved that among all α1-adrenoceptors, cardiac myocytes functionally express only α1A- and α1B-subtype. Scientists indicated that α1A-subtype blockade might be beneficial in restoring normal heart rhythm. Therefore, we aimed to determine the role of α1-adrenoceptors subtypes (i.e. α1A and α1B) in antiarrhythmic effect of six structurally similar derivatives of 2-methoxyphenylpiperazine. We compared the activity of studied compounds with carvedilol, which is β1- and α1-adrenoceptors blocker with antioxidant properties. To evaluate the affinity for adrenergic receptors, we used radioligand methods. We investigated selectivity at α1-adrenoceptors subtypes using functional bioassays. We tested antiarrhythmic activity in adrenaline-induced (20 µg/kg i.v.), calcium chloride-induced (140 and 25 mg/kg i.v.) and barium chloride-induced (32 and 10 mg/kg i.v.) arrhythmia models in rats. We also evaluated the influence of studied compounds on blood pressure in rats, as well as lipid peroxidation. All studied compounds showed high affinity towards α1-adrenoceptors but no affinity for β1 receptors. Biofunctional studies revealed that the tested compounds blocked α1A- stronger than α1B-adrenoceptors, but except for HBK-19 they antagonized α1A-adrenoceptor weaker than α1D-subtype. HBK-19 showed the greatest difference in pA2 values - it blocked α1A-adrenoceptors around sevenfold stronger than α1B subtype. All compounds showed prophylactic antiarrhythmic properties in adrenaline-induced arrhythmia, but only the activity of HBK-16, HBK-17, HBK-18 and HBK-19 (ED50=0.18-0.21) was comparable to that of carvedilol (ED50=0.36). All compounds reduced mortality in adrenaline-induced arrhythmia. HBK-16, HBK-17, HBK-18 and HBK-19 showed therapeutic antiarrhythmic properties in adrenaline-induced arrhythmia. None of the compounds showed activity in calcium chloride- or barium chloride-induced arrhythmias. HBK-16, HBK-17, HBK-18 and HBK-19 decreased heart rhythm at ED84. All compounds significantly lowered blood pressure in normotensive rats. HBK-18 showed the strongest hypotensive properties (the lowest active dose: 0.01 mg/kg). HBK-19 was the only compound in the group, which did not show hypotensive effect at antiarrhythmic doses. HBK-16, HBK-17, HBK-18, HBK-19 showed weak antioxidant properties. Our results indicate that the studied 2-methoxyphenylpiperazine derivatives that possessed stronger α1A-adrenolytic properties (i.e. HBK-16, HBK-17, HBK-18 and HBK-19) were the most compounds in adrenaline-induced arrhythmia. Thus, we suggest that the potent blockade of α1A-receptor subtype is essential to attenuate adrenaline-induced arrhythmia.